The Structural Politics of Totem and Taboo - Lorne, David (My University, 2009)
Freud's Totem and Taboo was one of the more controversial additions to the literature of religious theory. The two major hypotheses of the work are the parallel between ontogenetic and phylogenetic evolution, and the primal horde parricide. The first hypothesis has rarely been taken seriously. The second, although never verified with anthropological evidence, has generated further hypotheses based upon its value as a symbolic representation rather than an actual occurrence. Paul Roazen has suggested that the primal horde parricide hypothesis possesses characteristics similar to those of most social contract theories. He posited, in light of this, that Totem and Taboo ought to be considered a kind of social contract, although it has never been thought of this way.
The major school of philosophical thought which has continued to maintain interest in Totem and Taboo, long after the main anthropological assertions have been dispelled, is the French structuralist movement and its successors. Through the work of Levi-Strauss, carried on with theorists such as Lacan, Bataille, and Derrida, Totem and Taboo has maintained value as important work. The French structuralists have sustained a tradition that began with Rousseau of combining mathematical reasoning and linguistic theory together with anthropological speculation raised in Totem and Taboo. Thus in light of Roazen's hypothesis and the structuralist treatment of Totem and Taboo, together with Bryan Skyrms' s recent work on Rousseau and the mathematics of social contract theory, I posit that Totem and Taboo is comparable to Rousseau's Social Contract, in which human nature, politics, myth and mathematics merge. Implicitly Totem and Taboo contains a novel theory of the political development of society.
Keywords: religious theory, ontogenetic, phylogenetic evolution, primal horde parricide